The Experiences of Couples Affected by Stroke and Nurses Managing Patient Rehabilitation: A Descriptive Study in Singapore - SHEENA RAMAZANU (Wolters Kluwer Health, Inc, 2021)
10.1097/jnr.0000000000000392